Fabrication of biodegradable textile scaffold based on hydrophobized hyaluronic acid - Zapotocky, Vojtech; Pospisilova, Martina; Janouchova, Katerina; Svadlak, Daniel; Batova, Jana; Sogorkova, Jana; Cepa, Martin; Betak, Jiri; Stepankova, Veronika; Sulakova, Romana; Kulhanek, Jaromir; Pitucha, Tomas; et al. (International journal of biological macromolecules, 2017)
In this work, we report on the preparation of a novel biodegradable textile scaffold made of palmitoyl-hyaluronan (palHA). Monofilament fibres of palHA with a diameter of 120μm were prepared by wet spinning. The wet-spun fibres were subsequently processed into a warp-knitted textile. To find a compromise between swelling in water and degradability of the final textile scaffold, a series of palHA derivatives with different degrees of substitution of the palmitoyl chain was synthesized. Freeze-drying not only provided shape fixation, but also speeded up scaffold degradation in vitro. Fibronectin, fibrinogen, laminin and collagen IV were physically adsorbed on the textile surface to enhance cell adhesion on the material. The highest amount of adsorbed cell-adhesive proteins was achieved with fibronectin (89%), followed by fibrinogen (81%). Finally, textiles modified with fibronectin or fibrinogen both supported the adhesion and proliferation of normal human fibroblasts in vitro, proving to be a useful cellular scaffold for tissue engineering.
Keywords: Hydrophobic and Hydrophilic Interactions; Cell adhesion; lidé; Fibronectin; Tissue Scaffolds; buněčná adheze; Surface Properties; tkáňové inženýrství; Fibrinogen; Textiles; Palmitoyl-hyaluronan; Cell Adhesion; textilie; Wet-spinning; fibroblasty; biokompatibilní materiály; povrchové vlastnosti; Tissue Engineering; Fibroblasts; kyselina hyaluronová; Humans; tkáňové podpůrné struktury; Textile scaffold; Biocompatible Materials; Hyaluronic Acid; hydrofobní a hydrofilní interakce